Microfinance and health interventions: Factors influencing loan repayment success with young men in Dar es Salaam, Tanzania - Balvanz, Peter (Glob Public Health, 2018)
Poverty is associated with numerous poor health outcomes. Youth unemployment in Tanzania is approximately 13.7%, and concentrates in urban areas. These youth lack relevant job skills and access to financial capital. Microfinance continues to be implemented globally to address poverty, and increasingly has been linked to health interventions. Men less frequently are recipients of microfinance loans. We offered microcredit to young men in an area of Dar es Salaam with high poverty as part of a randomised controlled-trial to assess the efficacy of a microfinance and health leadership intervention in preventing STI acquisition. We used mixed methods to understand predictors of successful loan repayment. Our qualitative sub-study showed that leader influence, prior business experience, personal motivation, and planning facilitated repayment. Using a modified Poisson approach, our quantitative analysis showed that successful repayment was associated with business experience, education, increasing number of children, community of residence, percentage of network members trained in business, and repayment success of peer leaders. Our results suggest that enforcing group accountability and repayment rules, offering ongoing training, and using successful entrepreneurs as role models could increase repayment success in similar populations. These strategies could provide financial opportunity for men while minimizing risk for microfinance institutions.